I Will Give You My Vote but Not My Money: Preferences for Public versus Private Action in Addressing Social Issues. (12th March 2018) - Norwood, Franklin Bailey; Tonsor, Glynn; Lusk, Jayson L
Abstract: This study explores the extent to which individuals will support public action but, in its absence, will not commit their own voluntary efforts. An internet survey was administered to over 3, 500 individuals with hypothetical scenarios in which they could donate their own money toward a cause and/or support government action. When asked to choose between public or private action, most chose a combination of the two, suggesting that public and private partnerships are the preferred vehicle for solutions to social problems. Close to 20% indicated they would vote for laws to confront an issue but not contribute their own private donations.